Duodenal Tube Feeding: An Alternative Approach for Effectively Promoting Weight Gain in Children with Gastroesophageal Reflux and Congenital Heart Disease - Seiko Kuwata; Yoichi Iwamoto; Hirotaka Ishido; Mio Taketadu; Masanori Tamura; Hideaki Senzaki (Gastroenterology Research and Practice)
We tested whether duodenal tube feeding effectively improves the clinical symptoms and body weight gain in children with congenital heart disease (CHD) and gastroesophageal reflux (GER). In the retrospective analysis of 17 consecutive children with CHD who were treated with duodenal tube feeding for symptomatic GER, we found that clinical symptoms of persistent emesis or respiratory wheezing after feeding disappeared with duodenal tube feeding in all patients. Duodenal tube feeding facilitated a stable nutritional supply, resulting in marked improvement of weight gain from 6 to 21 g/day (). In a patient with trisomy 21 and persistent pulmonary hypertension after the closure of a ventricular septal defect, duodenal tube feeding ameliorated pulmonary hypertension, as evidenced by the improvement of the pressure gradient of tricuspid regurgitation from 77 to 41 mm Hg. In 14 of the 17 patients, the duodenal tube was successfully removed, with the spontaneous improvement of GER (median duration of duodenal tube feeding: 7 months). In conclusion, duodenal tube feeding improves the weight gain of infants with GER who need treatment for CHD-associated heart failure. It also allows for the improvement of pulmonary hypertension.